2019
DOI: 10.1002/rra.3486
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of littoral and deep water sampling methods for assessing macroinvertebrate assemblages along the longitudinal profile of a very large river (the Danube River, Europe)

Abstract: We comparatively examined the role of littoral and deep water sampling methods in assessing macroinvertebrate assemblages and in characterizing longitudinal changes in assemblage structure along >2,500-km-long course of the Danube River, Europe.The effectiveness of detecting taxa corresponded well with an inshore-offshore gradient in sampling (i.e., distance from shore). Nevertheless, each method (i.e., littoral multihabitat sampling, kick and sweep sampling, and deep water dredging) contributed to some degree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…We chose to compare Hess samples and rock baskets for a few reasons. Shallower areas in large rivers have been shown to have more species and bioassessment metrics responded more strongly compared to those calculated from invertebrates collected in deeper areas (Szekeres et al 2019). Dipnet and kicknet samples would be difficult to use because of the strong currents in the Snake River and our previous work showed that dipnet samples collected a subset of the invertebrate community (Tronstad et al 2020).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…We chose to compare Hess samples and rock baskets for a few reasons. Shallower areas in large rivers have been shown to have more species and bioassessment metrics responded more strongly compared to those calculated from invertebrates collected in deeper areas (Szekeres et al 2019). Dipnet and kicknet samples would be difficult to use because of the strong currents in the Snake River and our previous work showed that dipnet samples collected a subset of the invertebrate community (Tronstad et al 2020).…”
Section: Discussionmentioning
confidence: 92%
“…Aquatic invertebrates are commonly used to monitor lotic ecosystems and they are often collected using quantitative samplers, qualitative methods or artificial substrate in large rivers. A variety of samplers have been used to collect aquatic invertebrates in large rivers including Hess samplers, Hester-Dendy plates, rock baskets, kicknet sampling, grab samples (e.g., Ponar) and dipnet sampling (Bartsch et al 1998, Blocksom and Flotemersch 2005, Weigel and Dimick 2011, Hughes et al 2012, Neto et al 2014, Szekeres et al 2019. Hess and Ponar samplers collect aquatic invertebrates that live on natural substrate within a known area.…”
Section: Introductionmentioning
confidence: 99%
“…However, sampling at a variety of depths is important if the aim of the study is to collect across a diversity of species. 181 Sessile biota such as bivalves are easily collected by hand, either from the wild or from farmed areas. 173,182 Sampling offshore and at depth requires hook-and-line fishing, plankton or manta nets, or bongo nets depending on the size and life history of the study species.…”
Section: Biotamentioning
confidence: 99%
“…S2; methodology described in [16,17]; (ii) multihabitat sampling [18]; (iii) kick-and-sweep sampling [19]; (iv) detailed visual search and hand collection. Using such a detailed sampling procedure assured the best possible samples to assess the distribution of C. knipowitschii and its habitat preferences and to achieve confident data comparability since changing water levels and discharge greatly influence the sampling efficiency, especially in large rivers [19,20].…”
Section: Materials Collection and Sample Typesmentioning
confidence: 99%